Estimasi Kerugian Fisik Akibat Gempa Bumi pada Infrastruktur Jalan dan Jembatan: Studi Kasus Fly Over di Kota Bandung - Milyardi, Roi; Natanael, Ariel (Journal of Infrastructure Policy and Management, 2025)
Indonesia’s geographical location, which is prone to earthquakes and high economic losses in the infrastructure sector, requires a quantitative approach to support post-disaster financial resilience. This study aims to estimate earthquake losses to road and bridge infrastructure in a flyover in the City of Bandung using the HAZUS method developed by FEMA in the United States. The research methodology involved analyzing losses on the 550-meter flyover at the Jakarta street, the City of Bandung, which consisted of road and bridge segments. Estimates were made based on eight earthquake scenarios with different recurrence periods, using seismic parameters from the 2017 Indonesian Earthquake Map correlated to meet annual physical loss requirements (AAL). The analysis components included hazard (PGD and S1), fragility curves, and cost variables for each damage level. The results showed that the AAL values for sections AB, BC, and CD were IDR 23.46 million, IDR 14.29 million, and IDR 28.67 million, respectively. These findings indicate that the HAZUS method can be used to systematically map potential road infrastructure losses and support the planning of Disaster Pool Funding (PFB) allocations. Despite limitations in local data and design parameters, this study provides a strong basis for the development of more contextual and applicable loss estimation models in Indonesia.